Musculoskeletal Symptoms Among Finnish Professional Orchestra Musicians - Viljamaa, Katriina; Liira, Juha; Kaakkola, Seppo; Savolainen, Aslak (Medical problems of performing artists, 2017)
The prevalence of musculoskeletal symptoms is high among professional musicians (73-88%). We investigated the prevalence of musculoskeletal symptoms in Finnish symphony orchestra musicians. We compared individual instruments as well as the perceived demands of orchestral programs and difficulties in recovering after performances. In this cross-sectional questionnaire 920 of 2,785 members of the Finnish Musicians' Union (33%) completed the questionnaire, including 361 full-time members of symphony orchestras. Questions about pain symptoms and frequency were based on the national survey done in 2011. Among the 361 full-time orchestra musicians, those playing all instruments experienced frequent pain, both in the last 30 days and exceeding 30 days in the last 12 months, in their neck or upper extremities. Female musicians experienced significantly more neck (69%), elbow (31%), and wrist (30%) pain than males (neck 52%, elbow 23%, wrist 19%). The profiles varied according to the different instruments and their playing positions. Musculoskeletal symptoms correlated with perceived demand of the orchestral program and difficulties in recovering after performances. Professional musicians experienced nearly twice as often neck pain in the last 30 days (female musicians 69%, male musicians 52%) than persons of the same age in the Finnish working population (female 41%, male 27%). Symphony orchestra musicians experience nearly twice as much musculoskeletal symptoms of the neck and upper extremities as others their age. To prevent musicians' playing-related problems, special emphasis should be focused on recovery after concerts, including the special demands of different composers and the frequency of rehearsals and performances.